Wood's lamp for early detection of Microsporum Canis tinea capitis in children - Dexiang Sun; Jinming Lu; Tao Liu; Jun Wang (Photodiagnosis and Photodynamic Therapy)
Background: Pediatric alopecia is increasingly common, influenced by conditions like alopecia areata and infections such as tinea capitis, primarily caused by Microsporum canis. Diagnosing tinea capitis in primary care is challenging due to limited access to advanced tools, leading to treatment delays. Objectives: This study evaluates the effectiveness of Wood's lamp for early diagnosis of tinea capitis and its role in distinguishing it from other pediatric alopecia types. Methods: Fifty pediatric patients under 12 with alopecia were enrolled from March 2023 to March 2024. Data collected included contact history, CFW microscopy, fungal cultures, Wood's lamp examinations, treatments, and follow-ups. Results: Wood's lamp identified 22 cases linked to animal contact, confirmed as Microsporum canis. Overall, 30 tinea capitis, 15 alopecia areata, and 5 trichotillomania cases were diagnosed. Post-treatment, fluorescence decreased in tinea capitis patients, who also showed hair regrowth, with no recurrence during follow-up. Conclusions: Wood's lamp is a valuable, cost-effective diagnostic tool for tinea capitis, especially when combined with animal contact history, supporting its use in primary healthcare.